New broad-spectrum resistance to septoria tritici blotch derived from synthetic hexaploid wheat - Tabib Ghaffary, S.M.; Faris, J.D.; Friesen, T.L.; Visser, R.G.F.; Van Der Lee, T.A.J.; Olivier, R.; Kema, G.H.J.
Septoria tritici blotch (STB), caused by the ascomycete Mycosphaerella graminicola, is one of the most devastating foliar diseases of wheat. We screened five synthetic hexaploid wheats (SHs), 13 wheat varieties that represent the differential set of cultivars and two susceptible checks with a global set of 20 isolates and discovered exceptionally broad STB resistance in SHs. Subsequent development and analyses of recombinant inbred lines (RILs)from a cross between the SH M3 and the highly susceptible bread wheat cv. Kulm revealed two novel resistance loci on chromosomes 3D and 5A. The 3D resistance was expressed in the seedling and adult plant stages, and it controlled necrosis (N)and pycnidia (P)development as well as the latency periods of these parameters. This locus, which is closely linked to the microsatellite marker Xgwm494, was tentatively designated Stb16q and explained from 41 to 71percent of the phenotypic variation at seedling stage and 28-31percent in mature plants. The resistance locus on chromosome 5A was specifically expressed in the adult plant stage, associated with SSR marker Xhbg247, explained 12-32 percent of the variation in disease, was designated Stb17, and is the first unambiguously identified and named QTL for adult plant resistance to M. graminicola. Our results confirm that common wheat progenitors might be a rich source of new Stb resistance genes/QTLs that can be deployed in commercial breeding programs.